The effectiveness of inpatient physical therapy compared to outpatient physical therapy in older adults after total hip replacement in the post-discharge period: a systematic review - Klugarova, Jitka; Klugar, Miloslav; Mareckova, Jana; Gallo, Jiri; Kelnarova, Zuzana (JBI database of systematic reviews and implementation reports, 2016)
BACKGROUND: Total hip replacement is the most effective and safest method for treating severe degenerative, traumatic and other diseases of the hip joint. Total hip replacement can reliably relieve pain and improve function in the majority of patients for a period of 15 to 20 years or more postoperatively. Physical therapy follows each total hip replacement surgery. Physical therapy protocols after total hip replacement in the post-discharge period vary widely in terms of setting (inpatient, outpatient), content (the particular set of exercises used), and frequency (e.g. daily versus twice a week). In current literature, there is no systematic review which has compared the effectiveness of inpatient and outpatient physical therapy in patients after total hip replacement in the post-discharge period. OBJECTIVES: The objective of this systematic review was to compare the effectiveness of inpatient physical therapy with outpatient physical therapy on the quality of life and gait measures in older adults after total hip replacement in the post-discharge period. INCLUSION CRITERIA: This review considered studies that include older adults (over 65 years) who have had total hip replacement and are in the post-discharge period. Adults with bilateral or multiple simultaneous surgeries and also patients who have had hemiarthroplasty of the hip joint were excluded.This review considered studies that included any type of physical therapy delivered in inpatient settings provided by professionals with education in physical therapy. Inpatient physical therapy delivered at any frequency and over any duration was included.This review considered studies that included as a comparator any type of physical therapy delivered in outpatient settings provided by professionals with education in physical therapy or no physical therapy.This review considered studies that included the following primary and secondary outcomes. The primary outcome was quality of life, assessed by any validated assessment tool. The secondary outcome was measures of gait assessed by any valid methods.This review considered both experimental and observational study designs including randomized controlled trials, non-randomized controlled trials, quasi-experimental, before and after studies, prospective and retrospective cohort studies, case control studies and analytical cross sectional studies for inclusion. SEARCH STRATEGY: The search strategy aimed to find both published and unpublished studies. A three-step search strategy was utilized in 12 databases. Studies published in all languages and any date were considered for inclusion in this review. METHODOLOGICAL QUALITY: Assessment of methodological quality was not conducted as no studies were identified that met the inclusion criteria. DATA EXTRACTION AND SYNTHESIS: Data extraction and synthesis was not performed because no studies were included in this systematic review. RESULTS: During to the three-step search strategy 4330 papers were identified. The primary and secondary reviewer independently retrieved 42 potentially relevant papers according to the inclusion criteria by title and abstract screening. Following assessment of full text all of the retrieved papers were excluded based on the inclusion criteria. CONCLUSIONS: There is no scientific evidence comparing the effectiveness of inpatient physical therapy with outpatient physical therapy in older patients after total hip replacement in the post-discharge period. IMPLICATIONS FOR RESEARCH: This systematic review has identified gaps in the literature for comparing the effectiveness of inpatient physical therapy with and outpatient physical therapy on the quality of life and gait measures in older adults after total hip replacement in the post-discharge period. Prospective randomized double blind multicenter controlled trials are needed to answer this important clinical question.
Keywords: nerandomizované kontrolované studie jako téma; Randomized Controlled Trials as Topic; techniky fyzikální terapie; průřezové studie; kvalita života; lidé; Inpatients; dvojitá slepá metoda; hodnocení výsledků zdravotní péče; Physical Therapy Modalities; Aged, 80 and over; Non-Randomized Controlled Trials as Topic; retrospektivní studie; prospektivní studie; Cross-Sectional Studies; Double-Blind Method; pozorovací studie jako téma; Observational Studies as Topic; Aged; Prospective Studies; Outpatients; randomizované kontrolované studie jako téma; pacienti ambulantní; náhrada kyčelního kloubu; senioři nad 80 let; Arthroplasty, Replacement, Hip; senioři; Retrospective Studies; Quality of Life; hospitalizovaní pacienti; Outcome Assessment, Health Care; Humans